Simulated relaxation rate and local magnetic field distributions in porous systems - Benavides, A.; González, S.; Barrantes, D.; Martín Landrove, M. (Ciencia)
Numerical simulations of the nuclear magnetic relaxation process for fluids confined in the restricted geometry of the pore space were performed. The magnetic field fluctuations were calculated assuming an appropriate propagator for the molecules in the fluid and the geometry of the pore space. From the time series obtained, it was possible to calculate the spectral densities for the relaxation processes and the mean local magnetic field distribution function. The simulations are in accordance to experimental results.